A delicate balance: role of MMP-9 in brain development and pathophysiology of neurodevelopmental disorders - Reinhard, Sarah M.; Razak, Khaleel; Ethell, Iryna M. (Frontiers in Cellular Neuroscience, 2015)
The extracellular matrix (ECM) is a critical regulator of neural network development and plasticity. As neuronal circuits develop, the extracellular matrix stabilizes synaptic contacts, while its cleavage has both permissive and active roles in the regulation of plasticity. Matrix Metalloproteinase 9 (MMP-9) is a member of a large family of zinc-dependent endopeptidases that can cleave ECM and several cell surface receptors allowing for synaptic and circuit level reorganization. It is becoming increasingly clear that the regulated activity of MMP-9 is critical for central nervous system development. In particular, MMP-9 has a role in the development of sensory circuits during early postnatal periods, called ‘critical periods’. MMP-9 can regulate sensory-mediated, local circuit reorganization through its ability to control synaptogenesis, axonal pathfinding and myelination. Although activity-dependent activation of MMP-9 at specific synapses plays an important role in multiple plasticity mechanisms throughout the central nervous system, misregulated activation of the enzyme is implicated in a number of neurodegenerative disorders, including traumatic brain injury, multiple sclerosis, and Alzheimer’s disease. Growing evidence also suggests a role for MMP-9 in the pathophysiology of neurodevelopmental disorders including Fragile X Syndrome. This review outlines the various actions of MMP-9 during postnatal brain development, critical for future studies exploring novel therapeutic strategies for neurodevelopmental disorders.